On the issue of synthesis of linear invariant systems stabilization - Александрова, Татьяна Евгеньевна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
Proposed the technique of the synthesis of linear invariant stabilization systems, including the choice of weighting coefficients of the integral quadratic functional quality.